Utilization of narrow-land area to cultivate vegetables by verticulture system at Tongging village - Ginting, Herli; Sihotang, Brian Putra P.; Hashifatunnisa; Manik, Agatha Cristy (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Yard around the house has the potential to be supplied food for a family. The yard around as the most direct way of providing daily food and a source of income for the purchase of other foods. The yard around can provide enough nutritious food and income for the sale of yard around produce. To the scale of the families needed, yards around the house can be used to grow the fresh vegetables. However, the narrowyard is one of the problems for growing vegetables. The problem is bigger in the big cities. Verticulture is a system of agricultural cultivation where the planting area is arranged vertically or terraced to allow the efficiency of limited land. A limited land can produce the same as a normal land when the verticulture is used. Verticulture taken from English terms (vertical and culture) are cultivating agriculture systems that are placed vertically or tiered. One solution for the community can develop a farm for providing food of families with a verticulture system. Verticulture is a method of cultivation that the principle is efficiency use of land. Besides being cheap and easy to be done, gardening vegetables by a verticulture system also has several benefits and advantages. The benefits obtained are able to provide the family needed in vegetables and also make the atmosphere around the house to be more fresh. Aesthetically, vertically landscaped gardens serve as a backdrop that presents beautiful scenery in various colors. This program was conducted at Tongging village. Methods of this program by socialization with training and pamphlets and vegetables cultivation workshop verticulture and students of junior high scholl as participant. The results of this program that are students and their family can improve capability and skills in verticulture technology mastery such as preparation of planting media, planting and plant treatment, pest and disease control, harvesting and post-harvesting treatment.